2017
DOI: 10.1159/000470815
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein, a Natural Anti-Cancer Compound, Alters MicroRNA Expression Profiles in Bel-7402 Human Hepatocellular Carcinoma Cells

Abstract: Background/Aims: Baicalein has been shown to possess significant anti-hepatoma activity by inhibiting cell proliferation. Whether the anti-proliferative effect of baicalein is related to its modulation of miRNA expression in hepatocellular carcinoma (HCC) is still unknown. Methods: The anti-proliferative effects of baicalein on HCC cell line Bel-7402 was assessed by detecting the proliferation activity, cell cycle distribution, expression changes of p21/CDKN1A, P27/CDKN1B, total Akt and phosphoryted AKT. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…The modulatory effects of BAI on miRs have been reported in multiple diseases, such as pulmonary fibrosis, 15 hepatocellular carcinoma, 14 and bladder F I G U R E 5 miR-29 inhibitor reversed the repressive effects of BAI on the expression of collagen induced by TGF-β1. A, The accumulation of total soluble collagen decreased by BAI was promoted by miR-29 inhibitor in NIH-3T3 cells stimulated with TGF-β1.…”
Section: Discussionmentioning
confidence: 97%
“…The modulatory effects of BAI on miRs have been reported in multiple diseases, such as pulmonary fibrosis, 15 hepatocellular carcinoma, 14 and bladder F I G U R E 5 miR-29 inhibitor reversed the repressive effects of BAI on the expression of collagen induced by TGF-β1. A, The accumulation of total soluble collagen decreased by BAI was promoted by miR-29 inhibitor in NIH-3T3 cells stimulated with TGF-β1.…”
Section: Discussionmentioning
confidence: 97%
“…What's more, several studies have found that baicalein exerts antiinflammatory and anti-cancer effects in a broad spectrum of cancers [7].. For example, baicalein can induce apoptosis and inhibit metastasis of prostate cancer cells through inactivation of the caveolin-1/AKT/mTOR pathway [8]. Besides, it has been demonstrated that baicalein has efficient anticancer effects on hepatocellular carcinoma (HCC) to suppress cell growth and cell survival via the alteration of either microRNA [9] or mRNA expression profiles, the adjustment in the expression of CD24 included [10]. Beyond that, the activation of the AMPK/ULK1 pathway induced by baicalein is associated with a variety of human cancers [11].…”
Section: Original Papermentioning
confidence: 99%
“…After curative resection [3, 4], HCC frequently breaks out tumor recurrence and metastasis [5, 6]. Although much effort has been made, there are no effective therapeutic strategy to cure Hepatocellular carcinoma [7, 8]. Therefore, it is of great significance to identify the mechanism of migration and invasion and develop targeted therapeutics.…”
Section: Introductionmentioning
confidence: 99%